Meta-Evaluation Revisited - Michael Scriven (The Evaluation Center at Western Michigan University, 2009)
Next month will mark the passage of forty years since I published my first article about "meta-evaluation" (Scriven, 1969), a term I had invented somewhat earlier in a report to the Urban Institute, who had asked me for help in dealing with the noncomparability of the evaluations they had commissioned for several housing projects. This year also marks the elevation of the concept to the status of an independent category in the latest edition of the Program Evaluation Standards (Joint Committee, 1994). So the editors of  JMDE thought it might be time to take another look at this process and its products, and, as promised, we have provided a special section in this issue on the topic. Many thanks for the much-appreciated contributions that were sent in for that section! Before reading them, and hence without implying any criticism of them for ignoring or disagreeing with what follows, I'm going to mention some reflections on the notion that now seem to me worth stressing. They-and the other articles in this issue-may inspire reactions from you: Please put them on paper or screen, and we'd be happy to consider them for the (nonrefereed) discussion section of a later issue of JMDE.